Users’ Behaviour in Collaborative Tagging Systems - Chu, Samuel Kai Wah; Rathi, Dinesh; Du, Helen S. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study draws upon the work of Golder and Huberman (2005) and examines the users’ behaviour of two social bookmarking websites, Delicious and Connotea, by analyzing over 200,000 bookmarks from each website. The study also explores the cause(s) for similarity and difference in the behaviour of users of both websites. Basée sur les travaux de Golder et Huberman (2005), cette étude examine le comportement des usagers de deux sites web d'étiquetage social : Delicious et Connotea par l'analyse de plus de 200 000 signets dans chaque site. L'étude explore également les origines des similitudes et des différences dans le comportement des usagers des deux sites.